Penggunaan Multi Metode Untuk Strategis Perencanaan Sistem Informasi Pada Pusat Kesehatan Masyarakat - Rani Laple Satria Putra (KH. A. Wahab Hasbullah University, 2022)
The benefits of strategic planning of information systems are the creation of more effective, efficient and transparent activities. The results of the observations that have been made, the Air Beliti Health Center, Tuah Negeri District, Musi Rawas Regency has not implemented information system technology in carrying out its activities and there are still many activities that are done manually as a result making operational activities not run optimally. This paper will discuss the steps in strategic planning and in implementing information systems using the Ward and Peppard framework and analysis using the SWOT Analysis method, Value Chain Analysis and Mc Farlan Grid.